2014
DOI: 10.1051/matecconf/20141501019
|View full text |Cite
|
Sign up to set email alerts
|

Malaysian Scenario on Access and Facilities for Persons with Disabilities: A literature review

Abstract: Abstract. Physical barriers may hamper persons with disabilities (PWDs) movement in built environment. The needs of physical barrier-free environment are internationally acknowledged. This study explores the Malaysian scenario on access and facilities for PWDs by reviewing relevant legislation and guidelines, and literatures that examined the access and facilities provided in public buildings. This study identifies that Malaysia has plays its roles by establishing the relevant acts and legislation on PWDs need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…This is in-line with [10] stating that most of the public buildings in Malaysia are still lacking in the provision of user-friendly built environment for the disabled persons. Inaccessibility found in some stations is mainly due to poor design, poor planning, poor maintenance and lack of enforcement on guidelines provided.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in-line with [10] stating that most of the public buildings in Malaysia are still lacking in the provision of user-friendly built environment for the disabled persons. Inaccessibility found in some stations is mainly due to poor design, poor planning, poor maintenance and lack of enforcement on guidelines provided.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, [9] added that the simplest way of increasing the use of public transportation facilities is by establishing a safe, convenient and comfortable environment for the full participation of these citizens. However, several researchers revealed that the present provisions are inadequate and not disabled friendly [10,4,5]. This suggests for serious action to be taken by the government as the public facility provider.…”
Section: Persons With Disabilities (Pwd) Generallymentioning
confidence: 96%
“…The methodology approach is qualitative that will be participatory of actual PwDs of four (4) disabilities category with interviews to identify accessibility obstacles and narrative by explanatory of checklist items (Creswell, 2012). The qualitative research design is content analysis of regulatory documents relating to Universal Design and Mosque building typology with access audit checklist to measure the level of accessibility according to technical access designs, drawings and documents (Walliman, 2011) such as PwDs Act 2008, UBBL 34A, MS1184, MS2577 and JAKIM design guidelines as previously laid out in detail by these local researchers (Hussein & Yaacob, 2012;Kadir & Jamaludin, 2012a;Kamarudin, Ariff et al, 2014;Kamarudin, Hashim et al, 2012;Mahsa et al, 2015;Maidin, 2012;Nur Amirah, Ismail, et al, 2018a;Nur Amirah, Ismail et al, 2018b;Yusof & Jones, 2016). The findings analyzed within the capacity of a case study or a 'bounded system' of a specific case example of various state and heritage Mosque in Malaysia (Groat & Wang, 2002;Merriam, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In a multilevel building, there is a regulation that requires the developer to provide an elevator to physically handicapped people especially in a building where it is impractical to construct and build a wheelchair ramp [13]. In Malaysia, there are a few Malaysian standard codes of practice on access for disabled persons that specify the basic requirement of buildings and related facilities to permit access for disabled persons [14]. Apart from a person with a wheelchair, an elevator can also help elderly people and obese people to easily move in a multistoried building.…”
Section: Design Targetmentioning
confidence: 99%